Design and Planning (AL-Carmel) Neighborhood in Haska – Hebron - Zaidan, Ahmed (Palestine Polytechnic University, 2025)
Our project aims to design the infrastructure of the residential neighborhood in a modern, smart, and creative style, with a special focus on re-sorting and distributing land and designing road networks. The work team will use photogrammetry techniques in the first phase of the project to study and analyze the topography of the project site. In the second phase, we will use land rezoning laws to make more appropriate roads that match the topography of the project site, and then sort and distribute the lands so that they are better suited for the purpose. The study area for this project is Hebron (Haska), which has a total area of 700 dunums. As part of our study, we will check the accuracy of photogrammetry modeling elevations and compare them with GNSS RTK elevation results, ensuring acceptable accuracy levels as the basis for planning the neighborhood.
Number of pages: 1, 2025 Engineering for Palestine Conference (ENG4PAL) PPU, Hebron, Palestine, September 29-30, 2025
Keywords: Design, Planning, AL-Carmel, Neighborhood, Haska, Hebron